The Mitochondria–Endoplasmic Reticulum Contacts and Their Critical Role in Aging and Age-Associated Diseases - Moltedo, Ornella; Remondelli, Paolo; Amodio, Giuseppina (Frontiers in Cell and Developmental Biology, 2019)
The recent discovery of interconnections between the ER membrane and those of almost all the cell compartments is providing novel perspectives for the understanding of the molecular events underlying cellular mechanisms in both physiological and pathological conditions. In particular, growing evidences strongly support the idea that the molecular interactions occurring between Endoplasmic Reticulum (ER) and mitochondrial membranes, referred as the Mitochondria/Endoplasmic Reticulum Contacts (MERCs), may play a crucial role in ageing and in the development of age-associated diseases. As emerged in the last decade, MERCs behave as signalling hubs composed by structural components that act as critical players in different age-associated disorders, such as neurodegenerative diseases and motor disorders, cancer, metabolic syndrome, as well as cardiovascular diseases. Age-associated disorders often derive from mitochondrial or ER dysfunction as consequences of oxidative stress, mitochondrial DNA mutations, accumulation of misfolded proteins and defective organelle turnover. In this review, we discuss the recent advances associating MERCs to ageing in the context of ER-mitochondria crosstalk regulating redox signalling, ER-to mitochondria lipid transfer, mitochondrial dynamics and autophagy.